The algorithmic mediation of management fashions: authority, amplification, communication - Madsen, Dag Øivind; Slåtten, Kåre (Frontiers in Communication, 2025)
Management fashions have long been explained as the result of charismatic gurus, consultants, and professional media who confer legitimacy on new ideas. In the platform era, however, the circulation of management ideas is increasingly mediated by algorithms that privilege certain communicative forms while obscuring others. Building on management fashion theory, this paper conceptualizes algorithms as non-human actors that participate in the communicative construction of authority and legitimacy. The analysis draws on the concept of algorithmic meta-capital to explain how human actors navigate and exploit platform logics through reflexive adaptation. Using the diffusion of Agile as an illustrative example, the paper shows how visibility and meaning shift across platforms such as LinkedIn, YouTube, and TikTok. Legitimacy is reframed as a hybrid outcome of authenticity performance and algorithmic amplification, extending management fashion theory into the domain of organizational communication. Six propositions outline how algorithmic authority, amplification, and meta-capital reshape diffusion dynamics, communicative lifecycles, and the politics of visibility in the platform age.